Kinked and retained nasogastric tube in polytrauma patient - Ashok Kumar; Vardan Kulshreshtha; Pavan Kumar; Gaurav Jaiswal; Tarun Kumar Gupta (Romanian Neurosurgery, 2017)
Enteral feeding is an important and preferred technique of feeding in head injury patient to provide nutrition. As inadequate nutrition causes decrease in physical ability, neurological impairment and takes a long time for improvement or delayed deterioratation. With our best knowledge kinked and retained nasogastric tube in stomach is a very rare complication of feeding in head injuries patients. Predisposing factors that can cause kinking is excess tube length, tube in situ for long time and small bore tube. We are reporting one such case of kinked and retained nasogastric tube in the stomach of a polytrauma patient which was retrieved by upper GI endoscope.